Treatment of Delirium in Septic Shock Patients: A Focused Evidence Review (Medical Forum Monthly, 2026)
Objective: To review pharmacological and non-pharmacological strategies for established delirium in adults with septic shock.Place and Duration of Study: This review was conducted Intensive Care Medicine, Department of Adult Intensive Care Medicine, King Abdullah Specialized Hospital, Ministry of National Guards Health Affairs, Qassim, KSA.from January to March 2026.Methods: PubMed/MEDLINE was searched for studies published between 2021 and 2026 on septic shock, delirium, sepsis-associated encephalopathy, dexmedetomidine, antipsychotics, the ABCDEF bundle, early mobilization, and melatonin.Results: Dexmedetomidine may improve some organ-related outcomes but increases hypotension and has no consistent mortality or delirium benefit. Quetiapine and haloperidol show comparable efficacy for hyperactive delirium. ABCDEF bundle implementation improves long-term functional outcomes. Early mobilization appears feasible in hemodynamically stable patients, while melatonin improves sleep but has not consistently reduced delirium.Conclusion: No pharmacological therapy has demonstrated a clear mortality or delirium-resolution benefit in septicshock.